Identification of Heparan Sulfate in Dilated Cardiomyopathy by Integrated Bioinformatics Analysis - Song, Wenyu; Lu, Fujian; Ding, Zequan; Huang, Liqi; Hu, Kui; Chen, Jinmiao; Wei, Lai (Frontiers in Cardiovascular Medicine, 2022)
Objectives Heparan sulfate (HS) forms heparan sulfate proteoglycans (HSPGs), such as syndecans (SDCs) and glypicans (GPCs), to perform biological processes in the mammals. This study aimed to explore the role of HS in dilated cardiomyopathy (DCM). Methods Two high throughput RNA sequencing, two microarrays, and one single-cell RNA sequencing dataset of DCM hearts were downloaded from the Gene Expression Omnibus (GEO) database and integrated for bioinformatics analyses. Differential analysis, pathway enrichment, immunocytes infiltration, subtype identification, and single-cell RNA sequencing analysis were used in this study. Results The expression level of most HSPGs was significantly upregulated in DCM and was closely associated with immune activation, cardiac fibrosis, and heart failure. Syndecan2 (SDC2) was highly associated with collagen I and collagen III in cardiac fibroblasts of DCM hearts. HS biosynthetic pathway was activated, while the only enzyme to hydrolyze HS was downregulated. Based on the expression of HSPGs, patients with DCM were classified into three molecular subtypes, i.e., C1, C2, and C3. Cardiac fibrosis and heart failure were more severe in the C1 subtype. Conclusion Heparan sulfate is closely associated with immune activation, cardiac fibrosis, and heart failure in DCM. A novel molecular classification of patients with DCM is established based on HSPGs.